Difference Processing on Financial Accounting of Institutions and Enterprises - Hong-xia Liu (Progress in Machines and Systems, 2020)
In modern society, both enterprises and institutions would face a common problem which was how the accounting staff handle the finances. Due to the different properties, this two types of units could lead to the difference how to handle this units. This paper was to research and analyze problems from this aspect, and based on the analysis and research, and to compare the specific difference of institutions and enterprises, then put forward the corresponding point of view for research better understanding.